2005
DOI: 10.1001/archinte.165.13.1521
|View full text |Cite
|
Sign up to set email alerts
|

Management and Outcomes of Elderly Women and Men With Acute Coronary Syndromes in 2000 and 2002

Abstract: In the 2000s, elderly women and men with ACSs are receiving similar medical and invasive management during the index hospitalization; however, women with STE-ACS have higher mortality rates at 7 days but not at 6 months. Mortality rates are highest in patients with STE-ACS denied coronary angiography. The benefit of invasive procedures on mortality rates in elderly patients with STE-ACS needs further investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…That is precisely why those patients might benefit from a fast diagnosis and an accurate risk stratification. 21,22 These circumstances may further underline the meaning of this study as a "cross-sectional real world" registry.…”
Section: Discussionmentioning
confidence: 88%
“…That is precisely why those patients might benefit from a fast diagnosis and an accurate risk stratification. 21,22 These circumstances may further underline the meaning of this study as a "cross-sectional real world" registry.…”
Section: Discussionmentioning
confidence: 88%
“…A higher 1-year mortality was seen in women with AMI in the French USIC Registry, owing to a higher risk of death in women aged 30–67 years during the initial hospitalisation 39. However, another study showed a worse early outcome in elderly women with STE-ACS compared with men after adjustment for comorbidities, whereas similar outcomes were noted among patients with NSTE-ACS 40. Overall, our study showed similar outcomes for men and women after adjusting for clinical characteristics and ECG findings, whether or not PCI was included in the model.…”
Section: Discussionmentioning
confidence: 94%
“…Details of these nationwide surveys have been previously reported. 12,13 Briefly, ACSIS is a 2-month nationwide survey conducted biennially, which prospectively collects data from all acute coronary syndrome admissions in each of the 25 coronary care units and cardiology wards operating in Israel. Prespecified, standard forms were used to record demographic, clinical data management and outcome during the index hospital stay and subsequent follow-up.…”
Section: Acute Coronary Syndrome Israeli Surveysmentioning
confidence: 99%